Answer:
#8 might be y= -3x + 5
Step-by-step explanation:
This may help
Answer:
B
Step-by-step explanation:
(+)x(-)=(-)
(-)x(-)=(+)
Answer:
1.
Part A: Yes, it is (a - b)².
Part B: a² - 2ab + b² => (x - 6)² = x² - 12x + 36.
Part C: x² - 12x + 36.
2.
Part A: Not a special product.
Part B: Binomial distribution => (x + 8)(x + 1) = x² + 9x + 8.
Part C: x² + 9x + 8.
3.
Part A: Yes, it is (a + b)²
Part B: a² + 2ab + b² => (3x + 2)² = 9x² + 12x + 4.
Part C: 9x² + 12x + 4.
4.
Part A: Yes, it is (a + b)(a - b), a difference of squares.
Part B: a² - b² => 4x² - 49
Part C: 4x² - 49
5.
Part A: Not a special product.
Part B: Binomial distribution => (x - 5)(2x - 5) = 2x² - 15x + 25.
Part C: 2x² - 15x + 25
Step-by-step answer:
Given an enlargement from preimage (ABC) to image (A'B'C').
Need to find scale factor.
Solution:
Scale factor = linear size of image / linear size of preimage.
From the accompanying diagram, we see that
L(preimage) = AC = 4 units
L(image) = A'C' = 12 units
Therefore
Scale factor = L(image) / L(preimage) = 12 / 4 = 3